2020
DOI: 10.3151/jact.18.179
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Shear Capacity of Slender Reinforced Concrete Beams with Steel Fiber

Abstract: The objective of this research is to propose a simple and accurate prediction method for the shear capacity of reinforced concrete beams with steel fiber (RSF beams). Steel fiber reinforced concrete (SFRC) is being widely used nowadays, with the steel fibers added to the concrete to improve the tensile resistance. First, this research aims to investigate the material properties of SFRC in various concrete compressive strengths, shapes of steel fiber and volume fractions of steel fiber. In order to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Reinforced with a high dosage of discontinuous steel fibers, typical UHPC-class materials exhibit tensile strength exceeding 7.0 MPa (1.0 ksi) sustained well into the postcracking stress-strain regime. This behavior is shown to contribute significantly to the shear capacity of beams because fibers transmit forces across diagonal cracks, thus supplementing or even replacing the transverse reinforcement in resisting shear forces (Voo et al 2006;Voo and Foster 2008;Baby 2012;Kamal et al 2014;Pourbaba et al 2018;El-Helou and Graybeal 2019;Hemstapat et al 2020). Recent experimental investigations on UHPC beams and panel elements showed that, given the high compressive strength of UHPC, the shear failure is often controlled by the tensile behavior rather than compressive failure (Voo et al 2010;Baby et al 2014;Ahmad et al 2019;Yap 2020;El-Helou and Graybeal 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Reinforced with a high dosage of discontinuous steel fibers, typical UHPC-class materials exhibit tensile strength exceeding 7.0 MPa (1.0 ksi) sustained well into the postcracking stress-strain regime. This behavior is shown to contribute significantly to the shear capacity of beams because fibers transmit forces across diagonal cracks, thus supplementing or even replacing the transverse reinforcement in resisting shear forces (Voo et al 2006;Voo and Foster 2008;Baby 2012;Kamal et al 2014;Pourbaba et al 2018;El-Helou and Graybeal 2019;Hemstapat et al 2020). Recent experimental investigations on UHPC beams and panel elements showed that, given the high compressive strength of UHPC, the shear failure is often controlled by the tensile behavior rather than compressive failure (Voo et al 2010;Baby et al 2014;Ahmad et al 2019;Yap 2020;El-Helou and Graybeal 2022b).…”
Section: Introductionmentioning
confidence: 99%